Dentigerous cysts with exostosis of the temporal bone in horses – A new variant diagnosed by computed tomography. (3rd November 2021) - Heun, F.; Schwieder, A.; Hansmann, F.; Bienert‐Zeit, A.; Hellige, M.
Summary: The dentigerous cyst or temporal teratoma in horses is a well‐known congenital malformation that occurs in the temporal region and usually contains dental tissue. This case report describes two horses with a previously unreported variant of the dentigerous cyst associated with an exostosis arising from the temporal bone. The principal clinical sign was a draining tract opening at the margin of the right pinna in both horses. There was no evidence of an ectopic tooth on the radiographs or at ultrasonographic examination. Computed tomography combined with positive contrast sinography of the draining tract revealed bone formation arising from the supramastoid crest of the right temporal bone extending towards a cyst‐like structure but without direct connection in both cases. This bone formation was located at a site on the supramastoid crest, close to the external acoustic meatus, where ectopic teeth may also occur. Both cysts were removed surgically with a good long‐term outcome.